Is there a role for sigmoidoscopy in symptomatic patients? Analysis of a study correlating distal and proximal colonic neoplasias detected by colonoscopy in a symptomatic population - Binda,Vítor (2007)
BACKGROUND: Colonoscopy is the gold standard exam to investigate patients with colonic complaints. However, its availability is limited in developing countries. Sigmoidoscopy has been advocated as a first procedure in colorectal cancer screening strategies, in order to select those who need colonoscopy. AIM: To study the correlation between distal and proximal colonic neoplasias in symptomatic patients 50 years or older and patients 40 to 49 years old who underwent colonoscopy at a gastrointestinal endoscopy unit in 1999 and 2000 with the purpose to evaluate its role in a symptomatic population. METHODS: All colonoscopies performed in our Department in 1999-2000 were reviewed. The distal colon was defined as the colonic segment aboral to the splenic flexure. Advanced neoplasias were defined as adenomas larger than 10 millimeters and adenocarcinomas. RESULTS: Of the 2,701 colonoscopies retrieved, 1,125 were enrolled in this study. Prevalence rates for adenoma, advanced adenoma and carcinoma were 28.9%, 4.6% and 4% in the group of 830 patients 50 years or older (mean age 65 years, 491 women). The finding of one small (<10 mm) adenoma in the distal bowel doubled the likelihood of finding a proximal neoplasia (OR = 2.12, 95% CI, 1.27-3.54), and multiple (OR = 3.99, 95% CI, 1.72-9.28) or advanced (OR = 3.73, 95% CI, 1.81-7.7) adenomas increased this risk even further. Of the patients without adenoma or carcinoma in the distal colon, 1.93% had proximal advanced neoplasia. In the group of 40 to 49-year-old patients (n = 395; mean age 44.8 years, 208 women) the prevalence of adenomas (14.9%), advanced adenomas (3.4%), and carcinomas (1.7%) was lower. CONCLUSIONS: The likelihood of finding a proximal lesion is greater in patients with distal neoplasias. This likelihood is further increased when adenomas are multiple or larger than 10 mm. One out of 52 patients 50 years or older with an apparently normal distal colon has advanced proximal neoplasia. Sigmoidoscopy is not an adequate exam for symptomatic patients aged 50 years or older.